JAPAN’S ECONOMIC, SOCIAL, AND POLITICAL CONDITIONS DURING MEIJI AND TAISHO PERIODS: OSHIN - Theresia - Arianti (Japanese Department Faculty of Cultural Science Universitas 17 Agustus 1945 Surabaya, 2021)
Abstrak: Studi ini didasarkan pada serial TV Oshin yang disiarkan perdana pada 1983. Oshin, tokoh utama, lahir di Jepang pada tahun 1900 pada periode Meiji dan menghabiskan masa remajanya pada periode Taisho. Kebanyakan penelitian mengenai Jepang sebelumnya belum memasukan Oshin dan Face-Threatenig Acts sebagai landasan studi. Disinilah kekurangan yang akan diisi oleh studi ini dimana studi ini akan menunjukan sisi gelap Jepang pada periode Meiji dan Taisho melalui Face-Threatening Acts yang terdapat dalam dorama Oshin. Hasil studi menunjukan bahwa Jepang mengalami masalah kemiskinan pada zaman Meiji serta permasalahan politk pada zaman Taisho. Studi ini menunjukan bahwa Face-Threatening Acts dapat merepresentasikan latar belakang tempat dan waktu dari sebuah cerita.Kata kunci: Oshin, Face-Threatening Acts, periode Meiji, periode Taisho Abstract: This study is based on a Japanese TV series titled Oshin which was firstly aired in 1983. Oshin, the main character, was born in Japan in 1900 during Meiji period and spent her teenagehood in Taisho period. Previous studies examining Japan mostly do not include Oshin and Face Threatening Acts in the methods/materials used. These are the gaps the current study is fulfilling since this study aims to investigate Oshin’s portrayal of Japan, by using Face Threatening Acts theory, which can reveal Japan’s dark history to people outside Japan. Findings show that face threatening acts in the conversations amongst the characters reflect Japan’s poverty in Meiji period. The face threatening acts also reveal the “underground” political movement emerged in Taisho period as well as laborers’ bad working condition. This study shows how face threatening acts in a conversation can reflect the condition of the place and time when the conversation occurs. This study will also open the society’s eyes on what happened in Japan during Meiji and Taisho periods so that more people can learn from the history.Keywords: Oshin, Face-Threatening Acts, Meiji period, Taisho period